Cytotoxicity of SRJ23 and its derivatives, expression and SRJ23 binding of KRas G12V oncoprotein - Tan, Michelle Siying (2017)
Oncogenic KRas signaling is often associated with a poor prognosis of pancreatic cancer. Effort to target oncogenic KRas signaling persists for years but without much success due to its „undruggable‟ property. In recent years, several small-molecule KRas inhibitors such as SRJ23 were developed to inhibit oncogenic KRas signaling at the guanine nucleotide exchange level. MTT cell viability assay was used to evaluate the cytotoxicity of SRJ23 and its derivatives towards breast, colon, prostate and pancreatic cancer cell lines. SRJ23 is a semi-synthetic derivative of andrographolide (AGP) which lacks a distinct selectivity towards specific cancer type by demonstrating an equally good cytotoxicity in breast, colon, prostate, and pancreatic cancer cell lines. A few novel derivatives of SRJ23 were synthesised to improve its target specificity. One of the derivatives (SRS 151) shows selective total growth inhibition on pancreatic cancer cells harbouring oncogenic KRas (MIA PaCa-2 and Capan-2). SRS157 (GI50 = 2.4 μM), although is as equally potent as SRJ23 (GI50 = 2.1 μM) in pancreatic cancer cell lines, was found selectively targeting pancreatic cancer. Previous study has revealed a direct binding of SRJ23 to KRas in silico. To validate a physical interaction between oncogenic KRas G12V and SRJ23 in vitro, KRas G12V was expressed by using Champion pET SUMO protein expression system and was used for X-ray crystallography to study the physical interaction between KRas G12V and SRJ23. The hanging drop vapour diffusion method in X-ray crystallography did not yield diffractable protein crystals, therefore saturation transfer difference-nuclear magnetic resonance (STD-NMR) was applied to study KRas G12V-SRJ23 interaction. The STD-NMR suggested a potential physical interaction between KRas G12V and SRJ23 that involves mainly the three-membered ring and the hydroxyl group on the lactone ring of SRJ23. In conclusion, the findings of this study showed that SRJ23 could be a promising anti-Ras drug.